1979
DOI: 10.2466/pr0.1979.45.3.863
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Humanistic Approach on Students' Attitudes, Attributions, and Ethical Conflicts

Abstract: 22 graduate students in nursing, enrolled in a humanistic psychology course, were exposed to the principles of humanistic psychology and to a debunking of the medical model. Analyses of participants' pre-post responses on three self-report instruments indicated that the humanistic approach apparently increased students' humanistically oriented attitudes toward mental illness, positive attributions to mental patients, and reported ethical conflict in hypothesized clinical decision-making. Followup data generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
2
17
0
1
Order By: Relevance
“…An evidence-based approach to combating prejudice requires consideration of alternatives to promoting biogenetic causal theories. There is strong evidence that viewing ''psychiatric symptoms'' as understandable psychological or emotional reactions to life events is related to reduced fear, distance and discrimination (Arkar & Eker, 1996;Coker, 2005;Morrison, 1980;Morrison, Becker, & Bourgeois, 1979;Morrison & Teta, 1979, 1980Read & Harre, 2001;Read & Law, 1999;Walker & Read, 2002). The recent large German, Russian and Mongolian studies have confirmed this (Angermeyer & Matschinger, 1996a;Dietrich et al, 2004).…”
Section: Evidence-based Alternativesmentioning
confidence: 98%
“…An evidence-based approach to combating prejudice requires consideration of alternatives to promoting biogenetic causal theories. There is strong evidence that viewing ''psychiatric symptoms'' as understandable psychological or emotional reactions to life events is related to reduced fear, distance and discrimination (Arkar & Eker, 1996;Coker, 2005;Morrison, 1980;Morrison, Becker, & Bourgeois, 1979;Morrison & Teta, 1979, 1980Read & Harre, 2001;Read & Law, 1999;Walker & Read, 2002). The recent large German, Russian and Mongolian studies have confirmed this (Angermeyer & Matschinger, 1996a;Dietrich et al, 2004).…”
Section: Evidence-based Alternativesmentioning
confidence: 98%
“…Thus, the counselor in this situation may be vulnerable to making an ethical choice that on the surface seems to be insensitive. Moreover, differences in stages of moral reasoning may help explain the variability of the impact of training in ethics that has been noted by several researchers (Baldick, 1980;Granum & Erickson, 1976;Morrison & Teta, 1979;Shertzer & Morris, 1972).…”
Section: Sandersmentioning
confidence: 95%
“…There are data suggesting that certain courses increase participants' awareness of the ethical dimensions of their work. Morrison & Teta (1979) explored the impact of a humanistic psychology course on the attitudes of students in a related field (psychiatric nursing) toward ethically charged issues such as involuntary commitment and the right to refuse treatment. They reported significant gains in sensitivity to the ethical dimensions of such situations at the end of the course.…”
Section: The Impact Of Ethics Educationmentioning
confidence: 99%
“…In other words, there are no data that support the efficacy of ethics education in changing practitioners' responses with clients. The findings of Morrison and Teta (1979) and Paradise (1976) raise the question of whether formal discussion of ethics is essential or is only one way to increase ethical sensitivity. Discussion of ethics would perhaps be equally valuable if integrated throughout the graduate curriculum.…”
Section: The Impact Of Ethics Educationmentioning
confidence: 99%